HUBUNGAN PENGGUNAAN MASKER DENGAN KELUHAN SUBJEKTIF SISTEM PERNAFASAN PADA PEKERJA HOME INDUSTRY MEBEL DI DESA CIKEDUK KABUPATEN CIREBON - Siska Widiasari; Mitha Erlisya Puspandhani; Dede Setiawan (Jurnal Kesehatan Mahardika, 2021)
Physical Processes of processing raw materials to purify furniture can making the hazardous materials such as dust of wood. Workers who are in the area of higher dust levels can overcome complaints of respiratory caused by one of them from the use of masks. Based on a preliminary study 12 out of 16 furniture workers deal with the subjective complaints of respiratory system including coughing, phlegm, and shortness of breath.This purpose study to determine the correlation of the use of masks with a subjective complaints of respiratory system on furniture home industry workers in the Cikeduk Village, Cirebon District. The type of research used is descriptive correlation with retrospectively study design. The population in this study were all workers in 24 furniture home industries in Cikeduk Village totaling 232 workers with sample of 70 people. The sampling technique uses quota sampling. The statistical test used is Chi Square. The results obtained p value of 0,032 and smaller than the value of α = 0,05, this indicates a relationship use of the masks with subjective complaints of respiratory system on furniture home industry workers in the Cikeduk Village, Cirebon District. The need for workers to improve discipline in using masks so that it can help improve the subjective complaints of respiratory system and check their health with routine on health services.